Drought-induced production of reactive oxygen species and antioxidants activity of four local upland rice cultivars in Central Sulawesi, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Boy R, Indradewa D, Putra ETS, Kurniasih B. 2020. Drought-induced production of reactive oxygen species and antioxidants activity of four local upland rice cultivars in Central Sulawesi, Indonesia. Biodiversitas 21: 2555-2565. Drought can be the most severe threat to the production of crop in the world. This water deficit condition may cause a considerable decrease in yield grain of upland rice. Present study was conducted to figure out the level of ROS production and antioxidant activity on upland rice cultivars under drought stress. The experiment was performed using randomized completely block design with two factors, i.e. four cultivars of upland rice (Habo, Hiwanggu, Sunggul, and Lambara) and watering interval (once in one, two, four and eight days). The results showed that there was interaction between cultivars and watering intervals. Drought tolerant cultivars of Habo and Sunggul had higher activities of SOD, POD, AAred as well as ?-Toch with lower content on free radicals of O2- and H2O2; whereas non-drought tolerant cultivars of Hiwanggu and Lambara exhibited higher production of O2- and H2O2 and lower level of SOD, POD, AAred as well as ?-Toch. It could be concluded that the optimum soil moisture affecting maximum activities of SOD, POD, AAred as well as ?-Toch and minimum content of O2- and H2O2 was around 15.88-27.56% in range which was equal to 50.88-87.38% of field capacity.
Keywords: Antioxidant, drought, Oryza sativa, reactive oxygen species